Does Fecal Microbiota Transplant Have a Role in Treating Recurrent Clostridioides difficile Infection in Rural Hospitals? - Vedala, Krishna; Sobash, Philip; Shah, Parth; Kamoga, Gilbert-Roy (Frontiers in Public Health, 2021)
Clostridioides difficile infection possesses a significant economical burden, specifically in the inpatient and rural settings. Fecal Microbiota Transplant has been used for treatment of recurrent Clostridioides difficile but its utility is limited by current guidelines and resources. We conducted a retrospective chart review to evaluate the financial benefit of using Fecal Microbiota Transplant after first recurrence of Clostridioides difficile infection. We found that while its use was restricted, on average Fecal Microbiota Transplant can save 11,603.49 per patient. In conclusion, our study shows that using Fecal Microbiota Transplant could prove to be economically beneficial in treating recurrent CDI in rural hospitals.